Cognitive Control Signals in Posterior Cingulate Cortex - Hayden, Benjamin; Smith, David V.; Platt, Michael (Frontiers in Human Neuroscience, 2010)
Efficiently shifting between tasks is a central function of cognitive control. The role of the default network—a constellation of areas with high baseline activity that declines during task performance—in cognitive control remains poorly understood. We hypothesized that task switching demands cognitive control to shift the balance of processing towards the external world, and therefore predicted that switching between the two tasks would require suppression of activity of neurons within the CGp. To test this idea, we recorded the activity of single neurons in posterior cingulate cortex (CGp), a central node in the default network, in monkeys performing two interleaved tasks. As predicted, we found that basal levels of neuronal activity were reduced following a switch from one task to another and gradually returned to pre-switch baseline on subsequent trials. We failed to observe these effects in lateral intraparietal cortex (LIP), part of the dorsal fronto-parietal cortical attention network directly connected to CGp. These findings indicate that suppression of neuronal activity in CGp facilitates cognitive control, and suggest that activity in the default network reflects processes that directly compete with control processes elsewhere in the brain..